After America - Birmingham, John, 1964- (Ballantine Books, 2010)
Traces the harrowing reconstruction of the United States after most of its population is killed by a natural disaster, an effort lead by President James Kipper and challenged by pirates, freebooters, and a rogue governor of Texas.